Structure of visual biases revealed by individual differences. (June 2022) - Wexler, Mark; Mamassian, Pascal; Schütz, Alexander C.
Abstract: Multiple studies have shown that certain visual stimuli are perceived in accordance with strong biases that are both robust within individuals and highly variable from one individual to the next. These biases undergo small changes over time that demonstrate that they constitute latent states of the visual system. The literature to date indicates that the individual biases for different stimulus classes are independent of each other. Here we asked whether some of these biases are nonetheless related to one another. We measured individual biases for five classes of stimuli in 1000 participants. The stimuli were two different versions of two-dimensional apparent motion, smooth motion in Glass patterns, and two different structure-from-motion stimuli. There were pronounced individual biases in all stimuli, and these biases varied in direction and strength across individuals. Some biases were not independent: the two biases for apparent motion direction were most strongly correlated, and they were both correlated, but less strongly, to the bias direction for smooth motion. While all other pairs of biases had unrelated directions, the strengths of all biases were correlated. The correlation of bias strengths may be due to either a common factor across the stimulus types, or an attentional effect. Only a tiny fraction of the between-participant variance can be explained by age and gender. These results show that latent states of the visual system that we measure as individual biases are organized in a structured way, and call out for further study of this under-explored aspect of visual perception.